Molecular Characterization of Cephalosporin and Fluoroquinolone Resistant Salmonella Choleraesuis Isolated from Patients with Systemic Salmonellosis in Thailand - Pichapak Sriyapai; Chaiwat Pulsrikarn; Kosum Chansiri; Arin Nyamniyom; Thayat Sriyapai (MDPI AG, 2021)
The antimicrobial resistance of nontyphoidal Salmonella has become a major clinical and public health problem. Southeast Asia has a high level of multidrug-resistant Salmonella and isolates resistant to both fluoroquinolone and third-generation cephalosporins. The incidence of co-resistance to both drug classes is a serious therapeutic problem in Thailand. The aim of this study was to determine the antimicrobial resistance patterns, antimicrobial resistance genes and genotypic relatedness of third-generation cephalosporins and/or fluoroquinolone-resistant Salmonella Choleraesuis isolated from patients with systemic salmonellosis in Thailand. Antimicrobial susceptibility testing was performed using the agar disk diffusion method, and ESBL production was detected by the combination disc method. A molecular evaluation of S. Choleraesuis isolates was performed using PCR and DNA sequencing. Then, a genotypic relatedness study of S. Choleraesuis was performed by pulse field gel electrophoresis. All 62 cefotaxime-resistant S. Choleraesuis isolates obtained from 61 clinical specimens were multidrug resistant. Forty-four isolates (44/62, 71.0%) were positive for ESBL phenotypes. Based on the PCR sequencing, 21, 1, 13, 23, 20 and 6 ESBL-producing isolates harboured the ESBL genes blaCTX-M-14, blaCTX-M-15, blaCTX-M-55, blaCMY-2, blaACC-1 and blaTEM-1, respectively. This study also found that nine (9/62, 14.5%) isolates exhibited co-resistance to ciprofloxacin and cefotaxime. All of the co-resistant isolates harboured at least one PMQR gene. The qnr genes and the aac(6')-Ib-cr gene were the most prevalent genes detected. The QRDR mutation, including the gyrA (D87Y and D87G) and parC (T57S) genes, was also detected. PFGE patterns revealed a high degree of clonal diversity among the ESBL-producing isolates.